Nivel de conocimiento en salud bucal de los padre en relación a la higiene bucal de sus hijos preescolares del AAHH Puerto Morey – Belén - López Pérez, Noheli Sthefani (2024)
OBJECTIVE: The present study sought to determine the relationship between the level of oral health knowledge of parents and the oral hygiene of their preschool children in the AAHH Puerto Morey - Belen; in the year 2024. METHOD: The study was conducted using a quantitative approach. It was a non-experimental, cross-sectional, and correlational design. The sample consisted of 139 preschool children, aged between 2 and 6 years, residing in the AAHH Puerto Morey in the district of Belén. A questionnaire on oral health knowledge was administered to the parents, and the IHOS was used to assess the oral hygiene status of their children. RESULTS: It was found that the highest percentage of parents have an average knowledge of oral health, accounting for 79.9% of the total sample, while the IHOS results indicated that the children have good oral hygiene, with the highest percentage being 53.2%. According to the statistical data, it was demonstrated that there is no relationship between the parents' level of knowledge about oral health and the oral hygiene of their preschool children (p=0.127). CONCLUSIONS: Parents and/or guardians have an average level of knowledge about oral health; however, there is no relationship with the oral hygiene of their children since the oral hygiene index is good.